An overview of available metamaterial-based antenna for non-invasive hyperthermia cancer treatment - Nabilah Abdul Jaffar; Norlida Buniyamin; Kasumawati Lias (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the outcome of a literature review that an overview of various types of antenna and metamaterial applicator performance towards cancerous tissue or cell for non-invasive hyperthermia cancer treatment (NIHCT) procedure. From the review, it shows that when LHM lens integrated with an antenna, focusing capabilities of the antenna towards the cancerous area can be improved. However, current applicators have a poor focusing effect when directed towards the actual tumor area. In conjunction with that, this paper proposes a new design of modified applicator that is microstrip antenna integrated with left-handed metamaterial (LHM) lens. The antenna termed microstrip-LHM (M-LHM) lens antenna is proposed for use in NIHCT. It is expected to improve the focusing capabilities of an antenna which is used to kill the cancerous area and thus improve the hyperthermia cancer treatment procedure success rate. In addition, this paper provides an overview of heating techniques used in hyperthermia to enhance focusing capabilities and a few metamaterial advantages that can improve the focusing effect and reduced the hot-spots. Specific Absorption Rate (SAR) will be investigated to evaluate the focusing abilities of the proposed applicator using the SEMCAD X Solver.